In vitro effect of low-fluoride toothpastes containing sodium trimetaphosphate on enamel erosion - Cruz, Nathália Viana de Souza [UNESP]; Pessan, Juliano Pelim [UNESP]; Manarelli, Michele Maurício [UNESP]; Souza, Maria Daniela Basso de [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier B. V., 2015)
To evaluate the effect of a low-fluoride dentifrice (LFD) containing sodium trimetaphosphate (TMP) on enamel erosion in vitro. Bovine enamel blocks (n=144) were selected by surface hardness (SH) and subjected to erosive challenges, in two sets of experiments for 2 and 5 days. Blocks were randomly assigned to groups treated with slurries (5mL/block, for 15s) of following dentifrices: Placebo (no fluoride or TMP); LFD (250ppm F); LFD plus 0.25, 0.5, or 1.0% TMP; and a commercial positive control (1,425ppm F). The erosive challenge was produced by immersion in a soft drink (pH 2.8) for 5min, four times/day, interspersed by immersion in artificial saliva for 1h. SH and surface wear were analyzed as response variables. Data were submitted to 2-way ANOVA, followed by Student-Newman-Keuls test (p<0.05). All groups treated with LFDs containing TMP had significantly lower enamel wear when compared with the other groups tested (p<0.001). Also, the LFDs containing TPM at lower concentrations promoted SH similar to the commercial positive control, both being significantly higher than the LFD without TMP and Placebo (p<0.001). The supplementation of LFDs with TMP is able to significantly increase the anti-erosive potential of these formulations in vitro.
Keywords: Enamel; Erosion; Fluoride; Polyphosphates; Toothpaste